We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
98
3
avatar+895 

Find an expression for \(cos(5\theta)\) as a fifth-degree polynomial in the variable \(cos\theta\).

 May 11, 2019
edited by AdamTaurus  May 11, 2019
 #1
avatar+5662 
+1

CPhil is probably going to give you the proper answer so I'll chime in with a method that's probably

above where you're currently at but is one of the more clever tricks in the toolbox

 

.\(\cos(5\theta)= Re(e^{i5\theta}) = \\ Re((e^{i\theta})^5) = Re((\cos(\theta)+i\sin(\theta))^5)\\ \text{Now apply the binomial expansion}\\ Re\left(\sum \limits_{k=0}^5\dbinom{5}{k}\cos^k(\theta)(i\sin(\theta))^{5-k}\right)\)

 

\(\text{We can see the only terms that are real will be }k=1,3,5\\ \text{and we end up with}\\ \cos(5\theta) = \cos^5(\theta)-10\cos^3(\theta)\sin^2(\theta)+5\cos(\theta)\sin^4(\theta)\)

 

\(\text{Oh, I see you need it entirely in }\cos(\theta)\text{. Well we just do this}\\ \cos(5\theta) = \cos^5(\theta)-10\cos^3(\theta)(1-\cos^2(\theta))+ 5\cos(\theta)(1-\cos^2(\theta))^2\)

 

You can do the final simplification.

.
 May 11, 2019
edited by Rom  May 11, 2019
 #2
avatar+895 
+1

Yeah, that answer is smarter than I am.

AdamTaurus  May 11, 2019
 #3
avatar+102417 
+1

I'll use x instead of theta

 

cos (5x)  =     

cos(3x + 2x) = 

cos3xcos2x - sin3xsin2x =    

cos(x +2x)cos2x - sin(x +2x)sin2x  =        

[cosxcos2x - sinxsin2x]cos2x  - [sinxcos2x + sin2xcosx]sin2x  =   

cosxcos^2(2x) - sinxsin2xcos2x - sinxsin2xcos2x - cosxsin^2(2x) =   

cosx [ cos^2(2x) - sin^2(2x] - 2sinx [ sin2xcos2x] = 

cosx [cos^2(2x) - (1 - cos^2(2x) ] - 2sinx [ 2sinxcosx * (2cos^2x - 1) ]  =

cosx [ 2cos^2(2x) - 1] - 2sinx [ 4sinxcos^3x - 2sinxcosx ] = 

2cosx [cos(2x) ]^2 - cosx  -  8sin^2xcos^3x + 4sin^2xcosx = 

2cosx [ 2cos^2x - 1]^2 - cosx - 8[(1-cos^2x)cos^3x) ] + 4[(1-cos^2x )]cosx  = 

2cosx [ 4cos^4x - 4cos^2x + 1] - cosx - 8 [ cos^3x -cos^5x] + 4[ cosx - cos^3x ]  =

8cos^5x - 8cos^3x + 2cosx - cosx - 8cos^3x + 8cos^5x + 4cosx - 4cos^3x =

 

16cos^5(x) - 20cos^3(x) + 5cos(x)

 

Someone should verify this....I could have made an error....!!!!

 

 

cool cool cool

 May 11, 2019
edited by CPhill  May 11, 2019

13 Online Users